Halal Entrepreneurship Intention among Muslim Students: The Mediating Role of Attitude, Risk-Taking Propensity, and Self-Efficacy - Iskandar Iskandar; Pupu Saeful Rahmat; Sri Mulyati; Juliana Juliana; Asep Miftahuddin; Janah Sojanah; Shafinar Ismail; Inomjon Qudratov (UIN Sunan Gunung Djati Bandung, 2026)
Promoting halal businesses become urgent, as the global halal economy is projected to exceed USD 5 trillion by 2030, and Indonesia is of key contributor. However, despite the high entrepreneurial intention among university students, their participation in halal business activities is comparatively low. This study aims to examine the influence of religiosity on halal entrepreneurial intention in Indonesian Muslim students. Entrepreneurial attitudes, risk-taking propensity, and self-efficacy are considered as mediating variables between religiosity and halal entrepreneurial intention. Data were collected from 378 Muslim students at 47 private universities in West Java and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The structural model explained the variance in halal-based entrepreneurial intentions, with an R-squared of 0.654, indicating that religiosity and the mediator variables together explain approximately 65.4% of the variance in entrepreneurial intentions. The direct path coefficient demonstrates that religiosity significantly affects entrepreneurial attitudes (β = 0.606, p = 0.000), risk-taking propensity (β = 0.591, p = 0.000), self-efficacy (β = 0.653, p = 0.000), and intention to engage in halal entrepreneurship (β = 0.293, p = 0.000). All three mediating paths are statistically significant, with self-efficacy and entrepreneurial attitudes showing the strongest indirect effects (β = 0.156 each), followed by risk-taking propensity (β = 0.091). These results show that self-efficacy is the most influential factor, suggesting that higher religiosity is associated with greater self-confidence, moral resilience, and motivation for running a business in accordance with sharia principles. These findings extend the Theory of Planned Behavior (TPB) into an Islamic context and have implications for universities and policymakers in designing halal entrepreneurship education.